Human Alphacoronavirus Universal Primers for Genome Amplification and Sequencing - Choi, Sungmi; Kim, Kwan Woo; Ku, Keun Bon; Kim, Seong-Jun; Park, Changwoo; Park, Dongju; Kim, Seil; Yi, Hana (Frontiers in Microbiology, 2022)
To identify genetic variations of viral pathogens, rapid and accurate sequencing covering the entire genome is essential. However, sufficient amounts of viral nucleic acid for genome sequencing are not easily obtained from clinical specimens. Although various genome sequencing methods have been developed to overcome this issue, current methods available for alphacoronaviruses amplify a genome fragment using a strain-specific primer set. Since coronaviruses have a high mutation rate, new primers specific to the target strain must be continuously developed. Here, we designed a universal primer set and developed an optimal protocol that allows genome amplification and sequencing of all human alphacoronaviruses from samples with a minimum RNA template concentration of 102 copies/μL. The primer set is highly specific for human alphacoronaviruses and universal for the HCoV-like clade. We believe that our study makes a significant contribution to the literature because this method may enable faster diagnosis of mutant alphacoronaviruses in future epidemics.